Diversity Study of the Buterfly Species in Kallar, Kunjapanai and Kottagiri in Tamil Nadu - Dhivyasree, V.; Lekeshmanaswamy, M. (Indian Forester, 2021)
The present investigation has been carried out to enumerate the butterfly diversity that greatly depends on the availability of host plants. The study has been carried from Jan 2018 - December 2019 in three different regions such as Kallar, Kunjapanai and Kottagiriin Tamilnadu, India. During this study a total of 16396 butterflies representing 135 species and five families were identified. Larval host plants were identified for 135 butterfly species. Diversity indices such as Dominance species, Shannon index, Simpson index, Evenness and Fisher alpha Index were calculated seasonal wise. The butterfly species belonging to the nymphalidae family was found dominant in the three study areas. The butterfly diversity was maximum in the monsoon season when compared with pre monsoon, post monsoon and summer season.